Yoga Therapy for Pregnant Women to Overcome Stress in Premature Labor - Novida Ariani (Oshada, 2024)
Globally, prematurity stands as one of the leading causes of death in children under the age of five, making premature childbirth a significant concern worldwide, including in Indonesia. One of the key contributors to preterm labor is maternal stress, which triggers the activation of the hypothalamic-pituitary-adrenal (HPA) axis in both the mother and the fetus. As a preventive measure, complementary therapies such as yoga have been explored for their potential to alleviate stress and reduce the risk of premature labor. This article aims to examine the impact of yoga therapy on stress management in pregnant women, specifically in relation to preventing preterm births. The data for this study were gathered from electronic databases including Google Scholar, PubMed, and Science Direct, focusing on original research articles that explored the use of yoga therapy to manage stress in the context of premature labor. The search identified a total of 600 initial studies, with an additional 100 articles included later. After applying inclusion and exclusion criteria, 630 studies were excluded, and 70 articles were reviewed in full, resulting in 11 publications being utilized as references. The findings suggest a significant effect of yoga therapy in reducing the incidence of premature labor, highlighting its potential as a beneficial intervention for stress management in pregnant women.